Analysis of the words recorded as Turkmen in the Kitāb-i Mecmūʿi Tercümān-i türkį ve ʿAcemį ve Muġalį - Kassymova, M. (Journal of Oriental Studies, 2021)
When studying the territory of the distribution of the Turkic languages, it becomes obvious that the Kipchak-Turkic language covers a very vast territory, both in the historical period and today. Written sources that have survived from the Deshti-Kipchak region from the west of Central Asia to the banks of the Danube, the Middle Idil region in the north and the Crimea in the south, as well as the Turkic-Kipchaks, who ruled in the east for centuries, especially in Egypt and Syria, are quite rare. One of the most important written works of the Mamluk period that has survived to this day is Kitab-ı Mecmūʿı Tercümān-ı Türki ve ʿAcemį ve Muġalį. This work was written with the aim of teaching the Arabs the Turkic language, since in the Mamluk state the majority of the population were Arabs, and the ruling positions were occupied by the Turks. A handwritten copy of the work, written or copied in XIV century, is in the library of the Leiden Academy of the Netherlands. Kitab-ı Mecmūʿı Tercümān-ı Türki ve ʿAcemį ve Muġalį is a vocabulary and grammar guide organized by word types. One part of it, 63 pages, consists of the Arabic-Turkic dictionary and grammar, and the second - 13 pages, Mongolian-Persian words. In addition, the dictionary contains words written as Turkmen. We were able to determine that these words are used in the Turkic languages, while some of them underwent minor phonetic changes, as well as being transformed from one part of speech to another, acquired a new meaning. Key words: Kitāb-i Mecmūʿi Tercümān-i Türkį ve ʿAcemį ve Muġalį, Mamluks, Dictionary, Kipchak, the Kazakh language, Karluk, Turkmens.